Not duties but needs: rethinking refugeehood - Mantel, Susanne (Journal of ethics & social philosophy, 2019)
In the scholarly debate, refugeehood is often understood to arise from a special need for basic protection, i.e., for protection of basic needs and rights. However, the main definitions of refugeehood shift to duties when aiming to develop this view. Either, refugees are defined as all those individuals who can receive basic protection from the international community, and thus arguably ought to be protected, or refugees are defined as all those to whom a special form of protection, namely protection by admission is owed. The paper argues that either definition is incompatible with a commonsense desideratum on consistent and plausible criteria for refugeehood, since these definitions imply that refugeehood depends partly on the capacities of protecting states and on the needs of third parties. Instead, refugeehood is defined by the need for basic protection and by flight aiming to remedy this condition.
Online veröfffenlticht: 6. Mai 2019
Gesehen am 23.12.2025